Workshop Penulisan Artikel Ilmiah Jurnal Pengabdian kepada Masyarakat Dosen Universitas Ma’soem - Nur’aeni; Mimin Mintarsih; Eva Meidi Kulsum; Hidayatul Fikra; Fitriani (Gunung Djati Conference Series, 2022)
Universities more often hold training in writing research journal articles than training in writing journal articles for community service. This study aims to discuss efforts to increase the capacity of lecturers in the skills of writing journal articles for community service. This study uses the Participation Action Research method through a workshop approach involving 37 lecturers from various faculties at Ma'soem University. The results and discussion showed that the participants were enthusiastic about carrying out writing practices as an effort to increase the capacity of writing journal articles for community service through workshop activities. This study concludes that the implementation of the workshop was effective in an effort to increase the capacity of writing journal articles for community service at Ma'soem University lecturers. This study recommends the need for the preparation of modules for writing journal articles for community service in particular and the implementation of intensive training so that the skills capacity of lecturers become truly trained in writing community service journal articles.